Preauricular Transzygomatic Approach for Infratemporal Fossa and Surrounding Skull Base Lesion: An Institutional Experience - Jain, Rajat; Keshri, Amit; Manogaran, Ravi Shankar; Kumar, Raj; Keeranghat, Pearly Paptayil (Annals of Otology and Neurotology, 2018)
Background Preauricular transzygomatic surgical approach (PTZA) can be used to approach and resect tumors of infratemporal fossa (ITF) and surrounding skull base lesion. Various modifications in this approach can be used to approach various critical areas such as cavernous sinus, sphenoid sinus.Materials and Methods Clinical charts were reviewed to determine the association among pathological variables, surgical procedures, and outcomes.Results Three out of seven were malignant tumors and required pterional craniotomy and postoperative radiotherapy. 4 out of 7 were benign tumors and required craniofacial osteotomies.Conclusion PTZA is a versatile approach for tumor of ITF with or without intracranial extradural extension and cosmetically better than other approaches. This approach is better suited for lateral ITF tumors that are difficult to access through endoscopic approaches.
Keywords: infratemporal fossa; preauricular transzygomatic; pterional craniotomy